Coordinating abilities development in young hockey players taking into account power and weakness of nervous system - Mutaeva, I.; Petrov, R.; Kuznetsova, Z. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
The purpose of the manuscript is to study the indicators that characterize the development of young hockey players coordination abilities, depending on the strength and weakness of the nervous system properties manifestation to optimize training effects. The strength of athletes nervous system, in comparison with weakness, is characterized by its endurance to the effects of varying intensity physical exertion. There is the difference between the strength and weakness of the nervous system due to the manifestation of the excitation and inhibition process. Young athletes with a weak nervous system can quickly get excited, and then go into a slow state. Athletes with a strong nervous system train well, play effectively, and show stability in the manifestation of coordination abilities. We used the teppeng test method (Russia) to determine the properties of the nervous system. It allows us to quickly and accurately determine the individual characteristics of students nervous system. The main methodological approach is to differentiate training tools taking into account the strength and weakness of young hockey players nervous system. We defined seven significant factors, which perform the function of coordinating abilities markers, taken into consideration in sports training of young hockey players. The first place took the most important marker of coordinating abilities development in training of young hockey players: the age and identification of sensitive periods of coordinating abilities demonstration (1,09±0,02) and dependence on the characteristics of athletes` nervous system (1,12±0,02). An optimal ratio of the means in physical qualities complex development was the following: endurance - 25%; power 10%; flexibility- 10%; speed -25%; coordination - 30%.